Identification of deep intronic variants in junctional epidermolysis bullosa using genome sequencing and splicing assays - Fuying Chen; Ruoqu Wei; Yumeng Wang; Qiaoyu Cao; Jianbo Wang; Chenfei Wang; Dingjin Yao; Zhirong Yao; Cheng Ni; Ming Li (npj Genomic Medicine)
Abstract Junctional epidermolysis bullosa (JEB) is characterized by mucocutaneous fragility. We enrolled 69 cases of recessive JEB, with 13.0% of these cases remained genetically undiagnosed following an initial exome sequencing. Among cases carried COL17A1 variants, this proportion can reach 31.6%. We employed genome sequencing to genetically diagnosis these cases. Four deep intronic variants (c.4156+117 G > A, c.2039-104 G > A and c.1267+237dupC in the COL17A1 gene and c.-38 + 2 T > C in the LAMB3 gene) were identified in six cases. The c.4156+117 G > A variant was found in three of the five cases, suggesting it may be a common deep intronic variant in Chinese JEB. Splicing analysis revealed that these variants caused splicing defect by inducing exon skipping, or pseudoexon insertion into the transcript in HaCaT cells, not in HEK293 cells. Our results emphasize the importance of selecting the right cell line for mRNA analysis.